The Safety, Acceptability, and Feasibility of Single-Dose Rifampicin as Post-Exposure Chemoprophylaxis for Contacts of Leprosy Patients in Togo: A Mixed-Method Sequential Explanatory Study - Akila Wimima Bakoubayi; Falapalaki Haliba; Wendpouiré Ida C. Zida-Compaore; P’tanam P’kontème Bando; Yao Rodion Konu; Abissouwèssim Egbare Tchade; Kodjo Akpadja; Kamevor Alaglo; Maweke Tchalim; P’niwè Patchali; Yaovi Djakpa; Komi Amekuse; et al. (Tropical Medicine and Infectious Disease)
The World Health Organization is encouraging countries to include contact screening and single-dose rifampicin administration as preventive chemotherapy for contacts of leprosy patients in their leprosy control activities. However, no study has been conducted to assess the safety of SDR-PEP and the acceptability and feasibility of this intervention in Togo. To assess the safety of SDR-PEP, we used a cohort design, and for acceptability and feasibility, we used a mixed method, combining a quantitative study to assess the safety of SDR-PEP in a cohort of contacts from recently diagnosed leprosy patients followed by a qualitative study to identify the social, cultural, or institutional factors that would influence the adoption of single-dose rifampicin as post-exposure prophylaxis for contacts of leprosy patients in Togo. For the quantitative study, all identified index patients agreed to the disclosure of their status to their contacts and provided a list of their contacts. All the contacts found agreed to take part in the study, and an appointment was made for screening. However, some contacts were absent on the screening day for no reason. All eligible contacts agreed to take SDR and were followed up after taking the drug. No severe adverse events were reported during the follow-up. For the qualitative study, 72 interviews (66 semi-structured interviews and 6 focus groups) were carried out, and it emerged that, overall, opinions were favorable on the acceptability and feasibility of implementing single-dose rifampicin as post-exposure prophylaxis for contacts of leprosy patients in Togo. However, a number of conditions need to be considered for more effective results.